2002
DOI: 10.1046/j.1440-6055.2002.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of feeding efficiency, development time and survival of Tasmanian eucalyptus leaf beetle larvae Chrysophtharta bimaculata (Olivier) (Coleoptera: Chrysomelidae) on two hosts

Abstract: The native Eucalyptus leaf beetle Chrysophtharta bimaculata (Olivier) (Coleoptera: Chrysomelidae) has become a pest of the introduced, plantation species, Eucalyptus nitens Maiden in Tasmania, Australia. However, in the field it prefers to oviposit on the Tasmanian native species, E. regnans F. Muell. This laboratory study found that the performance of C. bimaculata larvae was superior on foliage of E. nitens compared with E. regnans. Larval development was 4 days shorter on E. nitens than on E. regnans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 31 publications
2
18
0
1
Order By: Relevance
“…Here, we examine the oviposition preference and larval performance between the two foliage types within one eucalypt host species, E. nitens. We confirm the findings of Lawrence et al (in press) for C. agricola's feeding preference for adult foliage in the field, and examine oviposition and larval performance in the laboratory to test the hypothesis that paropsine oviposition preference is often not explained by larval performance (Carne, 1966;de Little & Madden, 1975;Baker et al, 2002).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Here, we examine the oviposition preference and larval performance between the two foliage types within one eucalypt host species, E. nitens. We confirm the findings of Lawrence et al (in press) for C. agricola's feeding preference for adult foliage in the field, and examine oviposition and larval performance in the laboratory to test the hypothesis that paropsine oviposition preference is often not explained by larval performance (Carne, 1966;de Little & Madden, 1975;Baker et al, 2002).…”
Section: Introductionsupporting
confidence: 85%
“…To date, studies addressing oviposition preference and host choice in the Paropsini have focused on differences between host plant species (de Little & Madden, 1975;Steinbauer et al, 1998b;Howlett et al, 2001;Baker et al, 2002); rarely has the influence of intra-host foliage type on oviposition been considered (Steinbauer, 2002). Here, we examine the oviposition preference and larval performance between the two foliage types within one eucalypt host species, E. nitens.…”
Section: Introductionmentioning
confidence: 99%
“…Early paropsine instars experience high mortality under laboratory conditions in C. bimaculata (Baker et al, 2002) and C. agricola (Nahrung et al, 2001), and our overall egg-Liv field mortality estimates for P. atomaria were similar to these temperate species (de Little et al, 1990;Nahrung and Allen, 2004a, respectively). Our laboratory trials revealed relatively low survival rates for fourth instar larvae, exacerbated by higher rearing temperatures, especially above 24 8C.…”
Section: Development and Mortalitysupporting
confidence: 61%
“…Além desses fatores, existem diferenças na constituição de compostos secundários das folhas das espécies de eucalipto, como taninos, outros compostos fenólicos, gorduras e óleos essenciais, que influenciam negativamente o processo de herbivoria (ohmart; Edwards, 1991). BakEr et al (2002) Na comparação entre as espécies de eucalipto, E. camaldulensis apresentou a maior porcentagem de folhas sem danos (76,4%), diferindo dos demais materiais (Tabela 1). Essa espécie não apresentou folhas danificadas por C. ferruginea com notas acima de 5.…”
unclassified